Lipidized Prolactin-Releasing Peptide as a New Potential Tool to Treat Obesity and Type 2 Diabetes Mellitus: Preclinical Studies in Rodent Models - Mráziková, Lucia; Neprašová, Barbora; Mengr, Anna; Popelová, Andrea; Strnadová, Veronika; Holá, Lucie; Železná, Blanka; Kuneš, Jaroslav; Maletínská, Lenka (Frontiers in Pharmacology, 2021)
Obesity and type 2 diabetes mellitus (T2DM) are preconditions for the development of metabolic syndrome, which is reaching pandemic levels worldwide, but there are still only a few anti-obesity drugs available. One of the promising tools for the treatment of obesity and related metabolic complications is anorexigenic peptides, such as prolactin-releasing peptide (PrRP). PrRP is a centrally acting neuropeptide involved in food intake and body weight (BW) regulation. In its natural form, it has limitations for peripheral administration; thus, we designed analogs of PrRP lipidized at the N-terminal region that showed high binding affinities, increased stability and central anorexigenic effects after peripheral administration. In this review, we summarize the preclinical results of our chronic studies on the pharmacological role of the two most potent palmitoylated PrRP31 analogs in various mouse and rat models of obesity, glucose intolerance, and insulin resistance. We used mice and rats with diet-induced obesity fed a high-fat diet, which is considered to simulate the most common form of human obesity, or rodent models with leptin deficiency or disrupted leptin signaling in which long-term food intake regulation by leptin is distorted. The rodent models described in this review are models of metabolic syndrome with different severities, such as obesity or morbid obesity, prediabetes or diabetes and hypertension. We found that the effects of palmitoylated PrRP31 on food intake and BW but not on glucose intolerance require intact leptin signaling. Thus, palmitoylated PrRP31 analogs have potential as therapeutics for obesity and related metabolic complications.